Offshoring, domestic employment and production: Evidence from the German International Sourcing Survey - Wolfhard Kaus; Markus Zimmermann (Halle Institute for Economic Research (IWH), 2022)
This paper analyses the effect of offshoring (i.e., the relocation of activities previously performed in-house to foreign countries) on various firm outcomes (domestic employment, production, and productivity). It uses data from the International Sourcing Survey (ISS) 2017 for Germany, linked to other firm level data such as business register and ITGS data. First, we find that offshoring is a rare event: In the sample of firms with 50 or more persons employed, only about 3% of manufacturing firms and 1% of business service firms have performed offshoring in the period 2014-2016. Second, difference-in-differences propensity score matching estimates reveal a negative effect of offshoring on domestic employment and production. Most of this negative effect is not because the offshoring firms shrink, but rather because they don't grow as fast as the non-offshoring firms. We further decompose the underlying employment dynamics by using direct survey evidence on how many jobs the firms destroyed/created due to offshoring. Moreover, we do not find an effect on labour productivity, since the negative effect on domestic employment and production are more or less of the same size. Third, the German data confirm previous findings for Denmark that offshoring is associated with an increase in the share of 'produced goods imports', i.e. offshoring firms increase their imports for the same goods they continue to produce domestically. In contrast, it is not the case that offshoring firms increase the share of intermediate goods imports (a commonly used proxy for offshoring), as defined by the BEC Rev. 5 classification.
Keywords: D24; L60; O30; 330; international sourcing; offshoring; productivity